Poverty and undernutrition theory, measurement and policy - Svedberg, Peter (Oxford Oxford Univeristy Press, 2000)
A large share of population in many developing countries suffer from chronic undernutrition.This book provide a com- parative study of under nutrition in Sub-Sahara Africa and South Asia, the two worst affected areas and for all those concerned in develop
Keywords: Malnutrition-Africa, Sub-Saharan; Poor-Africa; Sub-Saharan-Nutrition